2013
DOI: 10.1016/j.jds.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of immediate and delayed post-space preparation using extended working time root canal sealers on apical leakage

Abstract: KEYWORDS apical seal; extended working time root canal sealers; post-space preparation; zinc oxideeeugenol sealerAbstract Background/purpose: The purpose of this study was to compare the effect of different post-space preparation time intervals on the apical sealing ability of filling material using two different extended setting time root canal sealers. Materials and methods: A total of 100 single-canal teeth were incrementally cleaned with crown-down instrumentation using K3 rotary nickeletitanium instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Immediate post space preparation by the same operator, who has just finished obturating the canal, can be done under rubber dam, using the same aseptic conditions and additional advantage of this protocol is that the condensation of the remaining gutta-percha can be assessed and improved if necessary. Finally the familiarity of the operator with the root canal system minimizes the risk of perforation or stripping [7,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediate post space preparation by the same operator, who has just finished obturating the canal, can be done under rubber dam, using the same aseptic conditions and additional advantage of this protocol is that the condensation of the remaining gutta-percha can be assessed and improved if necessary. Finally the familiarity of the operator with the root canal system minimizes the risk of perforation or stripping [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…They also found that leakage could occur at the interface between the sealer and dentin, sealer and gutta-percha, through the sealer itself, or by dissolution of the sealer [6]. In addition, One of the study compared two commonly used root canal sealers to evaluate whether post placement before or after the sealer setting shows a difference in post stability, and concluded that there is no significant difference [7]. Another study done with fiber post with 5-8 mm of gutta-percha & resin bonding sealer, there was 50 % improvement in prevention of leakage [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the residual filling may be dislodged, twisted or vibrated during postspace preparation which might create a pathway for bacterial invasion and reinfection of the root canal system. [ 1 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…Authors of the most previous studies agree that keeping 4–5 mm of the obturating material in the apical region constitutes a safe margin. [ 2 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…The objectives of endodontic therapy are to eliminate microorganisms from the root canal system, and to establish an effective barrier to prevent further passage of microorganisms or their byproducts to periapical tissues. 1 2 3 4 Thus, complete obturation of the root canal system and creation of an ‘apical’ seal are important for successful endodontic treatment. 5 6 7 8…”
Section: Introductionmentioning
confidence: 99%